Chlamydia screening in young people as an outcome of a HEADSS; Home, Education, Activities, Drug and alcohol use, Sexuality and Suicide youth psychosocial assessment tool. Issue 23 (19th September 2013) - Eade, Donna M; Henning, Dorothy
Abstract : Aims and objectives: To identify the percentage of young people presenting to a primary healthcare service targeting homeless youth, in Melbourne, Australia, who, based on youth‐specific Home, Education, Activities, Drug and alcohol use, Sexuality and Suicide (HEADSS) psychosocial assessment tool, were screened for the sexually transmitted infection Chlamydia and tested positive. Background: Homeless young people are at high risk of poor health outcomes including sexual health. Chlamydia prevalence is highest in 16–24 years. Youth psychosocial assessment tools such as the HEADSS can engage young people and provide comprehensive health assessment that identifies health risks. Design: A retrospective audit. Methods: One hundred consecutive client files of youth who presented to a primary healthcare service for the first time were selected. Client data were collected at the health services' inner city drop‐in clinic and clinical refuge outreach (CRO). HEADSS assessments were made on new presentations to identify those at risk of Chlamydia. These young people were then offered screening for Chlamydia using a first‐pass urine sample. Results: One hundred HEADSS assessments were audited, of which 15 were incomplete. Of the 85 completed HEADSS assessments, 43 were tested and 11 had Chlamydia‐positive results. Conclusion: Comprehensive youth assessment tools, such as the HEADSS, can provide a valuable resource in identifying sexual health risks such as Chlamydia. In turn, skilled nursing staff can provide opportunistic screening. Early identification and treatment for Chlamydia can reduce the spread and sequela of this highly infectious STI. Relevance to clinical practice: Youth health nurses can enhance their nursing practice in working with young people at risk of homelessness and improve their health outcomes by employing youth‐specific assessments.